2002
DOI: 10.1139/y01-088
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of rat lipoprotein lipid peroxidation by the oral administration of D003, a mixture of very long-chain saturated fatty acids

Abstract: Previous results have demonstrated that policosanol, a mixture of aliphatic primary alcohols isolated and purified from sugar cane wax, whose main component is octacosanol, inhibited lipid peroxidation in experimental models and human beings. D003 is a defined mixture of very long-chain saturated fatty acids, also isolated and purified from sugar cane wax, whose main component is octacosanoic acid followed by traicontanoic, dotriacontanoic, and tetracontanoic acids. Since very long-chain fatty acids are struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
1
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 53 publications
(53 reference statements)
3
32
1
2
Order By: Relevance
“…Cholesterol biosynthesis as measured using deuterium incorporation and gas chromatograph-mass spectrometry [39,50] did not support previous work, which demonstrated an inhibition of policosanols on cholesterol biosynthesis using indirect methods [5,18,19]. The present study showed increases in cholesterol biosynthesis in hamsters after supplementation with VLCFA.…”
Section: Discussioncontrasting
confidence: 99%
“…Cholesterol biosynthesis as measured using deuterium incorporation and gas chromatograph-mass spectrometry [39,50] did not support previous work, which demonstrated an inhibition of policosanols on cholesterol biosynthesis using indirect methods [5,18,19]. The present study showed increases in cholesterol biosynthesis in hamsters after supplementation with VLCFA.…”
Section: Discussioncontrasting
confidence: 99%
“…D-003 (5 and 10 mg/day) for 8 weeks led to results similar to the first trial. In addition, this trial revealed that D-003 also inhibits the susceptibility of LDL-C to lipid peroxidation, as demonstrated previously in experimental studies [32,33].…”
Section: Evidence From Clinical Studiessupporting
confidence: 84%
“…The extent of cellular lipid peroxidation was determined by measuring the concentrations of thiobarbituric acid-reactive substances (TBARS) as described by Menéndez et al 29) with minor modifications. Briefly, sample oxidation was terminated by adding butylated hydroxytoluene to the final concentration of 10 mM.…”
Section: Methodsmentioning
confidence: 99%